Primary Malignant Fibrous Histiocytoma of the Lung: A Case Report - I. Tsangaridou; G. Papamihalis; K. Stathopoulos; O. Konstantinopoulos; L. Thanos (Case Reports in Medicine)
Primary malignant fibrous histiocytoma (MFH) of the lung is extremely rare although it is among the most common soft tissue sarcomas in adults. Surgery is the primary mode of therapy, with high rates of local and distant recurrence, while radiation therapy appears to be a very useful adjunct, decreasing local relapse. We report a case of primary malignant fibrous histiocytoma of the lung. Fourteen years after surgical resection, the patient is still alive although with multiple metastatic lesions throughout his body.